Elaboración de un snack a base de lupino (chocho) y fécula de maíz - Solís García, Alison Ayli; Salvatierra Condoy, Sebastián David (Machala: Universidad Técnica de Machala, 2024)
The development of functional and healthy foods is a growing trend in the food industry. In this context, the present research focused on the creation of an innovative snack based on chocho (Lupinus mutabilis) flour and corn starch, addressing the need to offer products with high nutritional value and good sensory acceptance. The main objective was to evaluate the nutritional, sensory, and thermal characteristics of the snack to determine its viability as a competitive food product in the market. The methodology employed a mixture design to optimize the proportions of the ingredients, resulting in a formulation that stood out for its protein content (9.19%) and fat content (36.97%). Additionally, thermal properties were evaluated during the different stages of production, with variations observed in thermal conductivity and specific heat capacity, with frying being the stage where the highest heat transfer values were reached. The sensory evaluation identified formulation F2 as the most accepted, particularly in attributes such as color and crunchiness (p < 0.05), highlighting its potential to meet consumer expectations. The cost-benefit analysis revealed the economic viability of the project, with a positive Net Present Value (NPV) of $52,964.24 and an Internal Rate of Return (IRR) of 33%, suggesting high market competitiveness. In conclusion, the formulated snack not only meets nutritional and sensory standards but also presents itself as an economically viable option, standing out as a promising alternative in the offering of healthy and functional foods.
El desarrollo de alimentos funcionales y saludables es una tendencia creciente en la industria alimentaria. En este contexto, la presente investigación se centró en la elaboración de un snack innovador a base de harina de chocho (Lupinus mutabilis) y fécula de maíz, abordando la necesidad de ofrecer productos con alto valor nutricional y buena aceptación sensorial. El objetivo principal fue evaluar las características nutricionales, sensoriales y térmicas del snack para determinar su viabilidad como producto alimenticio competitivo en el mercado. La metodología empleó un diseño de mezclas para optimizar las proporciones de los ingredientes, resultando en una formulación que destacó por su contenido proteico (9,19 %) y su aporte graso (36,97 %). Además, se evaluaron las propiedades térmicas durante las diferentes etapas de elaboración, observándose variaciones en la conductividad térmica y la capacidad calorífica específica, siendo la fritura la etapa donde se alcanzaron los valores más altos de transferencia de calor. La evaluación sensorial identificó la formulación F2 como la más aceptada, especialmente en atributos como color y crocancia (p < 0,05), lo que subraya su potencial para satisfacer las expectativas de los consumidores. El análisis de costo-beneficio reveló la viabilidad económica del proyecto, con un Valor Actual Neto (VAN) positivo de $52 964,24 y una Tasa Interna de Retorno (TIR) del 33 %, lo que sugiere un alto potencial de competitividad en el mercado. En conclusión, el snack formulado no solo cumple con los estándares nutricionales y sensoriales, sino que también se presenta como una opción económicamente viable, destacándose como una alternativa prometedora en la oferta de alimentos saludables y funcionales.
Keywords: LUPINUS MUTABILIS; CHOCHO; FECULA DE MAIZ; SNACK